2017
DOI: 10.1159/000472261
|View full text |Cite
|
Sign up to set email alerts
|

Super-Selective Artery Embolization before Laparoscopic Partial Nephrectomy in Treating Renal Angiomyolipoma

Abstract: Introduction: To investigate the feasibility and efficiency of super-selective artery embolization (SAE) before laparoscopic partial nephrectomy (LPN) in treating renal angiomyolipoma (RAML). Materials and Methods: A retrospective analysis was conducted on 36 consecutive patients who underwent SAE before LPN (group A, n = 16) or LPN directly (group B, n = 20) from June 2010 to March 2016. Intraoperative blood loss, blood transfusion, operation time, warm ischemia time (WIT), and prognosis were compared between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
0
5
0
1
Order By: Relevance
“…However, to date, whether or not using NSS directly after SAE in treating AMLs differs in efficacy has not been demonstrated. One study [36] that included only 36 patients concluded that the application of SAE before LPN can decrease the difficulty of the surgery, the complications, and the risk of rebleeding. Additional studies are needed to provide evidence.…”
Section: Discussionmentioning
confidence: 99%
“…However, to date, whether or not using NSS directly after SAE in treating AMLs differs in efficacy has not been demonstrated. One study [36] that included only 36 patients concluded that the application of SAE before LPN can decrease the difficulty of the surgery, the complications, and the risk of rebleeding. Additional studies are needed to provide evidence.…”
Section: Discussionmentioning
confidence: 99%
“…Las opiniones sobre el papel de la EAR preoperatoria en el manejo de pacientes con patología tumoral renal aún son controvertidas, 5 sin poder hallar en la literatura un consenso sobre los beneficios y morbilidad asociados con el procedimiento. 9-11 A pesar de que se ha descrito la facilitación de la nefrectomía a través de la disminución de la pérdida de sangre, la facilidad de disección secundaria al edema en los planos tisulares y la disminución de los tiempos quirúrgicos con la EAR, 2,12 en el presente estudio se observó tendencia a mayor volumen de sangrado intraoperatorio y necesidad de transfusión en aquellos pacientes sometidos a embolización previa a la nefrectomía.…”
Section: Discussionunclassified
“…reported a study investigating the possibility of super-selective artery embolization of AML before partial nephrectomy in order to reduce morbidity and mortality during resection, especially for diameter >7 cm. 4 In our approach the patient underwent super-selective artery embolization in order to successfully treat acute bleeding, as the clinical practice suggests. 5 With our approach, 3 days after embolization she was able to complete a laparoscopic low anterior resection with primary re-anastomosis without any complications.…”
Section: Discussionmentioning
confidence: 99%